MAGA Republicans’ views of American democracy and society and support for political violence in the United States: Findings from a nationwide population-representative survey - Wintemute, Garen J.; Robinson, Sonia L.; Tomsich, Elizabeth A.; Tancredi, Daniel J. (PloS one, 2024)
Identifying groups at increased risk for political violence can support prevention efforts. We determine whether "Make America Great Again" (MAGA) Republicans, as defined, are potentially such a group. Nationwide survey conducted May 13-June 2, 2022 of adult members of the Ipsos KnowledgePanel. MAGA Republicans are defined as Republicans who voted for Donald Trump in the 2020 presidential election and deny the results of that election. Principal outcomes are weighted proportions of respondents who endorse political violence, are willing to engage in it, and consider it likely to occur. The analytic sample (n = 7,255) included 1,128 (15.0%) MAGA Republicans, 640 (8.3%) strong Republicans, 1,571 (21.3%) other Republicans, and 3,916 (55.3%) non-Republicans. MAGA Republicans were substantially more likely than others to agree strongly/very strongly that "in the next few years, there will be civil war in the United States" (MAGA Republicans, 30.3%, 95% CI 27.2%, 33.4%; strong Republicans, 7.5%, 95% CI 5.1%, 9.9%; other Republicans, 10.8%, 95% CI 9.0%, 12.6%; non-Republicans, 11.2%, 95% CI 10.0%, 12.3%; p < 0.001) and to consider violence usually/always justified to advance at least 1 of 17 specific political objectives (MAGA Republicans, 58.2%, 95% CI 55.0%, 61.4%; strong Republicans, 38.3%, 95% CI 34.2%, 42.4%; other Republicans, 31.5%, 95% CI 28.9%, 34.0%; non-Republicans, 25.1%, 95% CI 23.6%, 26.7%; p < 0.001). They were not more willing to engage personally in political violence. MAGA Republicans, as defined, are more likely than others to endorse political violence. They are not more willing to engage in such violence themselves; their endorsement may increase the risk that it will occur.